The Effect of Compensation, Work Discipline, and Work Motivation on the Performance of Non-Civil Servant Employees at the Secretariat Office of the Regional House of Representatives (DPRD) of Tanggamus Regency - Eliyanti, Eliyanti; Hasbullah, Hasbullah; Kumalasari, Nety (International Journal Of Education, Social Studies, And Management (IJESSM), 2026)
The purpose of this study is to examine the effect of compensation, work discipline, and work motivation on employee performance both simultaneously and partially. This research employs a quantitative approach with an associative design. The population consists of 137 non-civil servant employees, with a sample of 35 respondents selected using non-probability sampling techniques. Data were collected through questionnaires using a Likert scale and analyzed using multiple linear regression with SPSS version 23. The results show that compensation, work discipline, and work motivation simultaneously have a positive and significant effect on employee performance, as indicated by an F-value of 10.342, which is greater than the F-table value of 2.910, and a significant level of 0.000, which is less than 0.05. Partially, compensation has a positive and significant effect on performance, with a t-value of 3.528 greater than the t-table value of 2.0369 and a significance level of 0.037. Work discipline also shows a positive and significant effect, with a t-value of 3.716 and a significance level of 0.001. Furthermore, work motivation has a positive and significant effect on performance, with a t-value of 3.435 and a significance level of 0.006. Therefore, improving employee performance can be achieved through appropriate compensation, effective implementation of work discipline, and continuous enhancement of work motivation.